Life and labor on the internal colonial edge: Political economy of kolberi in Rojhelat. (10th March 2020) - Soleimani, Kamal; Mohammadpour, Ahmad
Abstract: Through the investigation of kolberi (cross‐border labor), this paper sheds light on the state's policy of de‐development (or internal colonialization) of the Kurdish region (known as Rojhelat) in Iran. While the most dangerous form of labor, kolberi has become a dominant employment opportunity for Rojhelat Kurds in the last decade. There are no Iranian state laws criminalizing kolberi, and yet those laborers die on a regular basis—being shot or thrown off mountain cliffs by the state forces, stepping into minefields, and so forth. Nevertheless, there is not a single scholarly paper on this subject. Using the mixed methods research approach, our study analyzes the existing data along with in‐depth interviews with 20 people who are currently engaged in kolberi to contextualize this understudied phenomenon. Our finding demonstrates that kolberi is a direct outcome of a uni‐ethno‐religious policies of development and part and parcel of the state's Perso‐Shi'ification strategy in Kurdistan. Therefore, kolberi is more of a political phenomenon than an economic one.